2020
DOI: 10.14336/ad.2019.0613
|View full text |Cite
|
Sign up to set email alerts
|

Lactulose Suppresses Osteoclastogenesis and Ameliorates Estrogen Deficiency-Induced Bone Loss in Mice

Abstract: Postmenopausal osteoporosis is characterized by excess osteoclastogenesis which leads to net bone loss and brittle fractures. Studies have demonstrated that estrogen deficiency-associated bone loss is microbiotadependent and could be prevented by probiotics and prebiotics. In this study, we report that orally administered lactulose (20 g/kg, 6 weeks) orally administered significantly inhibited osteoclastogenesis, bone resorption, and prevented ovariectomy (OVX)-induced bone loss in mice. Lactulose increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…Several studies have reported that short-term administration of inulin or lactulose increased Bi dobacterium spp. in the gut microbiota [10,20,21], which reduced bone resorption markers in postmenopausal women and healthy young men [22][23][24]; however, only limited studies have demonstrated that supplemented prebiotics change the gut microbiota and bone turnover metabolism markers in humans [24]. According to a consensus statement, prebiotics were recognized to particularly stimulate Bi dobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that short-term administration of inulin or lactulose increased Bi dobacterium spp. in the gut microbiota [10,20,21], which reduced bone resorption markers in postmenopausal women and healthy young men [22][23][24]; however, only limited studies have demonstrated that supplemented prebiotics change the gut microbiota and bone turnover metabolism markers in humans [24]. According to a consensus statement, prebiotics were recognized to particularly stimulate Bi dobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics, the substrates that promote the proliferation and metabolism of beneficial bacteria in the gut, also have a positive regulatory effect on calcium absorption and bone mass in postmenopausal women 96,97 . In OVX mice, prebiotics can normalize intestinal permeability, thereby decreasing exposure to GM, as well as inhibit the OVX‐induced, immune inflammation‐associated osteoclastogenesis via lowering the levels of pro‐osteoclastogenic cytokines, including TNF‐α, IL‐6, RANKL, and IL‐17, and increasing that of the anti‐inflammatory cytokine IL‐10 98 …”
Section: The Impacts Of the Gm On Bone Metabolismmentioning
confidence: 99%
“…96,97 In OVX mice, prebiotics can normalize intestinal permeability, thereby decreasing exposure to GM, as well as inhibit the OVX-induced, immune inflammation-associated osteoclastogenesis via lowering the levels of pro-osteoclastogenic cytokines, including TNF-α, IL-6, RANKL, and IL-17, and increasing that of the antiinflammatory cytokine IL-10. 98 Diabetes is a common endocrine-related disease closely linked with osteoporosis. 99,100 The GM plays a critical linking role between the two diseases.…”
Section: The Effects Of the Gm On Bone Metabolism In Diseasementioning
confidence: 99%
“…Twenty mice were randomly allocated into sham surgery (Control, Con) and ovariectomy (OVX) group according to their weight and random numbers were generated by Excel software. The procedure of OVX has been described previously [17]. Brie y, shave hair off the ank area of mice after its anesthesia with pentobarbital.…”
Section: Animals and Ovariectomy Model Establishmentmentioning
confidence: 99%